Recommended forages for Ethiopian environments and current strategies for utilization - Mengistu, A.; Lazier, John R. (French Grassland Society, 1989)
Discusses and lists forages recommended for Ethiopian environments and indicates current strategies for utilization out of the six identified by the Fourth Livestock Project Forage Development Programme.